Bowline on a Bight: Doing Right by the Records of Lilian Bland - Malek, Claire (Archivaria, 2022)
Focusing on a case study that has at its axis myself and the records of Lilian Bland, I explore person-centred archival theory by engaging primarily with what Sara Ahmed conceptualizes as queer use. I draw on recent archival literature on love and grief, queer theory, feminist theory, anti-colonial methods, and new materialism to propose a radical somatics of critical archival love. I situate my knowledge and power within discourses of social justice, healing, liberatory memory work, and gender and sexuality to reflect on what it means to “do right”: to act ethically and with care toward ourselves and the myriad others we encounter in archival practice, and to be of use to one another.